Deteksi Dini Penentu Kinerja Berbasis Intelektualitas dan Fasilitas - Nurhasanah, Nurhasanah; Meiliani, Endang; Suherman, Asep; Ratnawita, Ratnawita; Erna, Erna (Jurnal EMT KITA, 2026)
The shift in the modern work paradigm requires organizations to not only assess performance results but also detect performance potential early on. Individual performance no longer depends solely on personal abilities but also on environmental support and available facilities. A key challenge in human resource management is identifying the factors that determine performance before productivity declines. This study aims to develop an early detection model for performance determinants based on intellectuality and facilities, and to examine the extent to which these two factors contribute to performance simultaneously. The study used a quantitative approach with an explanatory research method through Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Data were collected through a questionnaire measuring intellectuality, facilities, and performance indicators using a five-point Likert scale. Data were then analyzed using validity, reliability, R-square, f-square, and bootstrapping tests. The results showed that intellectuality and facilities had a positive and significant effect on performance, with an R-square value of 0.647. Facilities had a slightly greater influence than intellectuality, indicating that facilities support is a key factor in realizing an individual's intellectual potential. The study concluded that early performance detection can be achieved through the integration of intellectual and facility aspects, not just through the evaluation of final results. The novelty of the study lies in a predictive model based on a combination of internal and external factors that can be used as a preventive monitoring system to maintain the stability and effectiveness of organizational performance.
Keywords: Intellectual; Facility; Performance; HR